Royalti Hak Cipta Sebagai Objek Harta Bersama Dalam Perceraian Berdasarkan Putusan Pengadilan Agama No. 1622/pdt.g/2023/PA. JB - Dewi Rinjani; Diana Tantri Cahyaningsih (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the position of copyright as joint property in marriage and to find out whether copyright can be used as an object of joint property dispute in divorce. The method used in this research is doctrinal legal research in the form of prescriptive legal research. The approaches used are a conceptual approach, a case approach and a statutory approach. The data collection technique used is in the form of library research. The results of this research show that basically copyright can be classified as immovable property based on the provisions of Article 499 of the Civil Code and Article 506 of the Civil Code. The status of copyright as property can give copyright the status of joint property if the copyright is registered during marriage. Copyright can become joint property in marriage because Article 199 of the Civil Code stipulates that all assets acquired during marriage will automatically become joint property. The use of economic rights in the form of copyright royalties must be used for mutual benefit as long as the husband and wife are still married. Copyright can also be used as an object of joint property dispute in a divorce if a husband and wife decide to divorce because joint property must be divided fairly if a divorce occurs as regulated in Article 37 of the Marriage Law. So that the position of copyright as an object of joint property in a divorce can be justified and considered valid because it has been regulated in law.